2021
DOI: 10.3389/fcomp.2021.775368
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning-based Sentiment Analysis and Topic Modeling on Tourism During Covid-19 Pandemic

Abstract: The Covid-19 pandemic has disrupted the world economy and significantly influenced the tourism industry. Millions of people have shared their emotions, views, facts, and circumstances on numerous social media platforms, which has resulted in a massive flow of information. The high-density social media data has drawn many researchers to extract valuable information and understand the user’s emotions during the pandemic time. The research looks at the data collected from the micro-blogging site Twitter for the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…Thus, researchers are putting their attention on developing the deep learning model to diagnose the disease accurately. For various medical image analysis problems such as CT scans, MRIs, X-rays, ultrasounds, and sentiment analysis [ 13 ], deep learning models have attained significant success [ 14 ]. It has demonstrated notable results for distinct disease detection and classification in the domain of the lungs, abdomen, brain, cardiovascular, retina, and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, researchers are putting their attention on developing the deep learning model to diagnose the disease accurately. For various medical image analysis problems such as CT scans, MRIs, X-rays, ultrasounds, and sentiment analysis [ 13 ], deep learning models have attained significant success [ 14 ]. It has demonstrated notable results for distinct disease detection and classification in the domain of the lungs, abdomen, brain, cardiovascular, retina, and so forth.…”
Section: Introductionmentioning
confidence: 99%
“… Rustam et al, (2021) identified sentiments regarding Covid-19 from tweets using a supervised machine learning approach to understand how people made informed decisions on how to handle their circumstances during the pandemic. Mishra et al, (2021) used LDA model on almost 20,000 tweets for tourism sector, sub-domains hospitality and healthcare during Covid-19 pandemic to identify frequent terms and applied state-of-the-art deep learning algorithm to generate a robust sentiment prediction model. This study contributes to this research stream by analyzing 1,251,216 Covid-19-related tweets from January 20, 2020, to May 29, 2021 to investigate Twitter users’ opinion and feeling about the Covid-19 pandemic during different phases of the pandemic, including the early stage of the disease, during the lockdown, and after the distribution of vaccines.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is the fourth largest economic activity (Cvelbar & Ogorevc, 2020) and the growth of this sector is very important for the world economy ( Kar et al, 2021 ). Additionally, this sector has grown tremendously from the last decade ( Mishra et al, 2020 ) and it is quite important for economic development ( Mishra et al, 2021 ). On the other hand, the sector that has suffered the most due to the COVID-19 pandemic is the tourism sector ( Han et al, 2020 ; Mishra et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%